Owen Lovejoy and the Coalition for Equality : Clergy, African Americans, and Women United for Abolition - Moore, Jane Anne; Moore, William F. (University of Illinois Press, 2019)
"Antislavery white clergy and their congregations. Radicalized abolitionist women. African Americans committed to ending slavery through constitutional political action. These diverse groups attributed their common vision of a nation free from slavery to strong political and religious values. Owen Lovejoy's gregarious personality, formidable oratorical talent, probing political analysis, and profound religious convictions made him the powerful leader the coalition needed. Owen Lovejoy and the Coalition for Equality examines how these three distinct groups merged their agendas into a single antislavery, religious, political campaign for equality with Lovejoy at the helm. Combining scholarly biography, historiography, and primary source material, Jane Ann and William F. Moore demonstrate Lovejoy's crucial role in nineteenth-century politics, the rise of antislavery sentiment in religious spaces, and the emerging commitment to end slavery in Congress. Their compelling account explores how the immorality of slavery became a touchstone of political and religious action in the United States through the efforts of a synergetic coalition led by an essential abolitionist figure."--